CRISPR/Cas9 Genome Editing in LGMD2A/R1 Patient-Derived Induced Pluripotent Stem and Skeletal Muscle Progenitor Cells - Lampros Mavrommatis; Abdul Zaben; Urs Kindler; Marie-Cécile Kienitz; Julienne Dietz; Hyun-Woo Jeong; Pierre Böhme; Beate Brand-Saberi; Matthias Vorgerd; Holm Zaehres (Hindawi Limited, 2023)
Large numbers of Calpain 3 (CAPN3) mutations cause recessive forms of limb-girdle muscular dystrophy (LGMD2A/LGMDR1) with selective atrophy of the proximal limb muscles. We have generated induced pluripotent stem cells (iPSC) from a patient with two mutations in exon 3 and exon 4 at the calpain 3 locus (W130C, 550delA). Two different strategies to rescue these mutations are devised: (i) on the level of LGMD2A-iPSC, we combined CRISPR/Cas9 genome targeting with a FACS and Tet transactivator-based biallelic selection strategy, which resulted in a new functional chimeric exon 3-4 without the two CAPN3 mutations. (ii) On the level of LGMD2A-iPSC-derived CD82+/Pax7+ myogenic progenitor cells, we demonstrate CRISPR/Cas9 mediated rescue of the highly prevalent exon 4 CAPN3 mutation. The first strategy specifically provides isogenic LGMD2A corrected iPSC for disease modelling, and the second strategy can be further elaborated for potential translational approaches.